The effects of formalisation, hierarchical decentralisation and lateral communication: Strategic decision-making processes on SME international performance - Dimitratos, Pavlos; Thanos, Ioannis C.; Petrou, Andreas; Papadakis, Vassilis M. (My University, 2011)
Purpose: This chapter seeks to examine the relationship between three strategic decision-making processes (SDMPs) and international performance of small- and medium-sized enterprises (SMEs). Methodology/approach: Drawing on a sample of 528 SMEs based in four countries (United States, United Kingdom, Greece and Cyprus), the chapter explores the relationship between formalisation, (hierarchical) decentralisation, lateral communication and international performance. The chapter also investigates the moderating effects of dynamism on the aforementioned relationship. Findings - Results indicate that formalisation and decentralisation have a positive effect on international performance, whereas lateral communication has no effect. Some evidence exists to support the moderating role of dynamism on the process-international performance link in that decentralisation produces positive effects in stable settings whereas lateral communication produces positive effects in dynamic ones. Research limitations/implications - This chapter focuses on three SDMP dimensions and one characteristic of the external environment. Future studies are also needed to replicate the findings reported here in other national settings. Also, future studies should consider additional variables. Practical implications - International performance of the SME can be influenced by how managers are involved in their SDMPs. Social implications - Given the high role that SMEs have in modern economies for employment and growth, we identify SDMPs that are conducive to their international performance. Originality/value - This study lies at the intersection of two streams of two complementary streams of research: strategic decision-making and international entrepreneur ship. It is one of the first attempts to involve the SDMP stream of research in internationalisation. 2011 by Emerald Group Publishing Limited.
Keywords: Cross-national study; Economics and Business; Environmental dynamism; SME internationalisation; Strategic decision-making processes